Single crystal of a one-dimensional metallo-covalent organic framework - Hai-Sen Xu (Nature Portfolio, 2020)
Although polymers have been studied for well over a century, there are few examples of covalently linked polymer crystals synthesized directly from solution. Here, the authors demonstrate a strategy to synthesize single crystalline 1D metallo-covalent organic frameworks by combining dynamic covalent chemistry and metal-ligand coordination.